Antihypertensive drug valsartan as a novel BDK inhibitor. (May 2021) - Kitaura, Yasuyuki; Shindo, Daichi; Ogawa, Tatsuya; Sato, Ayato; Shimomura, Yoshiharu
Abstract: Catabolism of branched-chain amino acids (BCAAs) is affected by various physiological conditions and its abnormality is associated with glucose metabolism, heart disease, and neurological dysfunction. The first two steps of the BCAA metabolic pathway are common to the three BCAAs (leucine, isoleucine, and valine). The second step is an irreversible rate-limited reaction catalyzed by branched-chain α-keto acid dehydrogenase (BCKDH), which is bound to a specific kinase, BCKDH kinase (BDK), and inactivated by phosphorylation. Here, we investigated potential new BDK inhibitors and discovered valsartan, an angiotensin II type 1 receptor (AT1R) blocker, as a new BDK inhibitor. BCKDH phosphorylation and the BCKDH-BDK interaction were inhibited by valsartan in vitro . Valsartan administration in rats resulted in increased BCKDH activity by decreasing the dephosphorylated level of BCKDH complex, bound forms of BDK from BCKDH complex as well as decreased plasma BCAA concentrations. Valsartan is a novel BDK inhibitor that competes with ATP, via a different mechanism from allosteric inhibitors. The BDK inhibitor has been shown to preserve cardiac function in pressure overload-induced heart failure mice and to attenuate insulin resistance in obese mice. Our findings suggest that valsartan is a potent seed compound for developing a powerful BDK inhibitor and useful medication for treating heart failure and metabolic diseases with suppressed BCAA catabolism. Graphical Abstract: ga1 Highlights: Valsartan was identified as an ATP-competitive inhibitor of BDK from an existing drug library. Valsartan decreased phosphorylation and disrupted BCKDH-BDK interaction in purified BCKDH 4 complex. Valsartan administration increased hepatic BCKDH activity as well as decreased plasma BCAA concentration in rats.